2023
DOI: 10.3847/1538-4357/acebce
|View full text |Cite
|
Sign up to set email alerts
|

Observation of Gamma Rays up to 320 TeV from the Middle-aged TeV Pulsar Wind Nebula HESS J1849−000

Abstract: Gamma rays from HESS J1849−000, a middle-aged TeV pulsar wind nebula (PWN), are observed by the Tibet air shower array and the muon detector array. The detection significance of gamma rays reaches 4.0σ and 4.4σ levels above 25 TeV and 100 TeV, respectively, in units of the Gaussian standard deviation σ. The energy spectrum measured between 40 TeV < E < 320 TeV for the first time is described with a simple power-law function of dN … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 50 publications
1
8
0
Order By: Relevance
“…Our estimate of e,max g corresponds to a maximum electron energy of E e,max » 400 TeV, which is comparable to the 740 TeV inferred from modeling the TeV emission of G32.6 (Amenomori et al 2023). With the lack of measurements at >20 keV, our estimation of E e,max should be regarded as a lower limit.…”
Section: Sed Modelingsupporting
confidence: 63%
See 1 more Smart Citation
“…Our estimate of e,max g corresponds to a maximum electron energy of E e,max » 400 TeV, which is comparable to the 740 TeV inferred from modeling the TeV emission of G32.6 (Amenomori et al 2023). With the lack of measurements at >20 keV, our estimation of E e,max should be regarded as a lower limit.…”
Section: Sed Modelingsupporting
confidence: 63%
“…-, and characteristic age τ c = 43 kyr, thus categorizing the point source as an energetic and middle-aged pulsar. Furthermore, this middle-aged pulsar and its PWN are of particular interest as their emission is significantly detected above 100 TeV by HAWC (Albert et al 2020), LHAASO (Cao et al 2023), and the Tibet air shower array (Tibet ASγ; Amenomori et al 2023) with a maximum photon energy of 350 TeV (Cao et al 2021). This indicates the presence of energetic particles within the PWN (G32.64+0.53, 8 hereafter G32.6).…”
Section: Introductionmentioning
confidence: 88%
“…As for the observed multiband data, the X-ray data are taken from Gagnon et al (2023), Fermi-LAT upper limits are taken from Eagle (2022), TeV data are taken from H.E.S.S. Collaboration (2018b) and Amenomori et al (2023), and PeV data are taken from Cao et al (2024). Furthermore, the X-ray images have revealed the angular radius θ X−ray ∼150″ (Gotthelf et al 2011;Gagnon et al 2023;Kim et al 2024) and the corresponding radius R X−ray ∼5.0 pc for the distance of 7.0 kpc.…”
Section: Resultsmentioning
confidence: 99%
“…However, at energies above 100 TeV, the CMB radiation dominates the γ-ray photon production (for details, see 1 PeV e 0.77 (Cao et al 2021b). Amenomori et al (2023) measured the spectrum of HESS J1849-000 at TeV energies and found no evidence of cut-off up to 740 TeV, which implies the corresponding electron energy of E e ; 1.7 PeV. Furthermore, the LHAASO observation detects γ-ray photons up to 1.9 PeV (Cao et al 2024), and it implies the corresponding electron energy of E e ; 3.5 PeV.…”
Section: Collaboration 2018b)mentioning
confidence: 99%
See 1 more Smart Citation